2023
DOI: 10.35848/1882-0786/acb2af
|View full text |Cite
|
Sign up to set email alerts
|

InGaN-based LEDs on convex lens-shaped GaN arrays toward multiwavelength light emitters

Abstract: InGaN-based light-emitting diodes (LEDs) on convex lens-shaped GaN microstructures are fabricated. The gently sloping microstructures enable us to employ simple device processes similar to those for conventional planar LEDs. The fabricated LEDs show a clear rectifying property and broadband electroluminescence spectra ranging from ~380 to ~500 nm due to the multiwavelength emission properties of the InGaN quantum wells. Furthermore, the peak wavelength continuously changes from ~470 to ~410 nm within a particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…InGaN-based multiwavelength emitters using local offangle variations have been demonstrated [49][50][51][52][53][54]. One method to realize local off-angle variations is patterning of GaN (0001) with grayscale lithography and dry etching [49][50][51][52].…”
Section: A Novel Approach For Polychromatic Emission Without Using Sagmentioning
confidence: 99%
See 3 more Smart Citations
“…InGaN-based multiwavelength emitters using local offangle variations have been demonstrated [49][50][51][52][53][54]. One method to realize local off-angle variations is patterning of GaN (0001) with grayscale lithography and dry etching [49][50][51][52].…”
Section: A Novel Approach For Polychromatic Emission Without Using Sagmentioning
confidence: 99%
“…Very recently, we proposed convex-lens-shaped 3D GaN microstructures for underlying layers of InGaN QWs [53,54]. Figure 20(a) shows the fabrication procedure for such QWs, which are referred to as microlens QWs.…”
Section: A Novel Approach For Polychromatic Emission Without Using Sagmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14] Similarly, it has been reported that LEDs with different emission wavelengths can be formed simultaneously on the growth surface by applying the difference in In uptake efficiency due to the three-dimensional structure with different facets or off angles. [15][16][17][18][19][20] Although these technologies enable different wavelengths to be integrated on a wafer, they present challenges such as fine processing and growth technologies and design constraints for controlling wavelengths. The second approach is to stack layers emitting different wavelengths in the growth direction.…”
Section: Introductionmentioning
confidence: 99%